The Dissemination of Clinical Practice Guidelines to Arthritis Health Professionals Using Innovative Strategies - De Angelis, Gino (Université d'Ottawa / University of Ottawa, 2018)
Problem: With an increasing aging Canadian population with chronic diseases such as arthritis, there is an urgent need for health professionals to promote evidence-based arthritis self-management support to their patients. Objective: The overall objective of this thesis was to determine the feasibility of using Facebook as a dissemination strategy for an online evidence-based arthritis self-management program, People Getting a Grip on Arthritis (PGrip), by arthritis health professionals with their patients. Methods: To identify the current evidence and knowledge gaps in regards to the use of innovative dissemination strategies for clinical practice guidelines (CPGs) and social media use for chronic disease self-management among health professionals, two systematic reviews of the literature were conducted. The first systematic review identified research on health professionals’ perceived usability and practice behaviour change of information and communication technologies (ICTs) for the dissemination of CPGs. The second identified research on the perceived usability of social media by health professionals to facilitate chronic disease self-management with their patients. To engage potential knowledge users in the research process, an advisory committee consisting of six arthritis health professional users (two registered nurses, two physiotherapists, and two occupational therapists) was convened to identify barriers and facilitators of using and accessing Facebook as a dissemination strategy for PGrip. The advisory committee was also convened to identify how the PGrip Facebook group page could be tailored to improve usability among arthritis health professionals. A feasibility study of 78 arthritis health professionals was then conducted to determine the feasibility of using Facebook as a dissemination strategy for PGrip among arthritis health professionals to their patients. To guide future research, a protocol for a pilot randomized controlled trial (RCT) was developed that will compare Facebook with an educational website and email to determine which strategy will demonstrate greater perceived usefulness among arthritis health professionals to disseminate the PGrip program with their patients. Results: The findings of the first systematic review revealed that health professionals’ perceived usability and practice behaviour change varies by type of ICT and the heterogeneity and paucity of properly conducted studies did not allow for a clear comparison between studies. The second systematic review revealed that health professionals perceived discussion forums and collaborative projects to be useful social media platforms to facilitate chronic disease self-management with patients. The feasibility study suggested that a Facebook group page can be used as a dissemination strategy for the PGrip program by arthritis health professionals. The Facebook group page was perceived to be usable with patients after two weeks and three months in regards its ease of use and high output quality. Conclusion: The overall research of this thesis provides advanced knowledge on how a Facebook group page as a dissemination strategy for an evidence-based self-management program for patients is perceived by arthritis health professionals. Facebook may provide arthritis health professionals with an additional option of how to best share evidence-based information to allow their patients to successfully self-manage their arthritis. A future pilot RCT is needed to determine whether Facebook is superior to other ICT intervention in regards its perceived usefulness among arthritis health professionals to disseminate the PGrip program with their patients.
Keywords: Clinical Practice Guidelines; Social Media; Self-management; Osteoarthritis; Rheumatoid Arthritis; Dissemination